Angiopoietin 2 Induces Glioma Cell Invasion by Stimulating Matrix Metalloprotease 2 Expression through the α(v)β(1) Integrin and Focal Adhesion Kinase Signaling Pathway - Hu, Bo (2006)
Accumulating evidence reveals a significant correlation between angiopoietin 2 (Ang2) expression and tumor invasion and metastasis in various human cancers, but the major focus of recent studies has been on the angiogenic effects of Ang2. We recently reported that Ang2-stimulated glioma cell invasion results from the up-regulation and activation of matrix metalloprotease 2 (MMP-2) in tumor cells. In this study, we identify a novel mechanism by which Ang2 stimulates MMP-2 expression leading to glioma cell invasion. We show that Ang2 interacts with α(v)β(1) integrin in Tie2-deficient human glioma cells, activating focal adhesion kinase (FAK), p130(Cas), extracellular signal–regulated protein kinase (ERK) 1/2, and c-jun NH(2)-terminal kinase (JNK) and substantially enhancing MMP-2 expression and secretion. The Ang2/α(v)β(1) integrin signaling pathway was attenuated by functional inhibition of β(1) and α(v) integrins, FAK, p130(Cas), ERK1/2, and JNK. Furthermore, expression of a negative regulator of FAK, FAK-related nonkinase, by U87MG/Ang2–expressing glioma xenografts suppressed Ang2-induced MMP-2 expression and glioma cell infiltration in the murine brain. These data establish a functional link between Ang2 interaction with α(v)β(1) integrin and glioma cell invasion through the FAK/p130(Cas)/ERK1/2 and JNK-mediated signaling pathway.